2017
DOI: 10.1177/1352458517694431
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Nocardia beijingensis infection associated with the use of alemtuzumab in a patient with multiple sclerosis

Abstract: Nocardia is a Gram-positive aerobic pathogen that usually affects immunocompromised patients. We report a case of pulmonary infection caused by a rare Nocardia species, Nocardia beijingensis, in a 50-year-old woman who had received alemtuzumab for the treatment of her multiple sclerosis. The invasive pulmonary infection was successfully treated with meropenem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…In the United States (US), a rare pathogen, Nocardia beijingensis , was isolated from a patient diagnosed with sepsis secondary to pneumonia 6 weeks after completing the first course of alemtuzumab; the patient responded well to treatment. 46 Finally, several cases of Listeria monocytogenes infection have been reported. In one case, the patient had recent exposure to foods including smoked sausage and soft cheese and developed Listeria septicemia after the initial alemtuzumab infusion.…”
Section: Safety In Long-term Clinical Trials and In Real-world Experimentioning
confidence: 99%
“…In the United States (US), a rare pathogen, Nocardia beijingensis , was isolated from a patient diagnosed with sepsis secondary to pneumonia 6 weeks after completing the first course of alemtuzumab; the patient responded well to treatment. 46 Finally, several cases of Listeria monocytogenes infection have been reported. In one case, the patient had recent exposure to foods including smoked sausage and soft cheese and developed Listeria septicemia after the initial alemtuzumab infusion.…”
Section: Safety In Long-term Clinical Trials and In Real-world Experimentioning
confidence: 99%
“…, called Nocardia beijingesis , was reported in a woman after alemtuzumab treatment. The woman recovered after intravenous antibiotic therapy (meropenem) 25. No cases of progressive multifocal leukoencephalopathy have been reported in RRMS patients treated with alemtuzumab.…”
Section: Methodsmentioning
confidence: 95%
“…In fact, the effects of live viral vaccines on the immune system after treatment with alemtuzumab are yet to be evaluated. Several cases of opportunistic infections, such as listeria meningitis, were reported 7,25. A single case of cerebral nocardiosis in a woman treated with alemtuzumab for RRMS was also observed 24.…”
Section: Methodsmentioning
confidence: 98%
“…14 Administration of live vaccines is not recommended since effects are yet to be further investigated. 14 In MS, listeria meningitis was also reported in several cases with alemtuzumab 24 mg, 57 59 such as single cases of cerebral nocardiosis, 60 and Nocardia beijingesis . 58 In two pivotal studies, one case was reported in the CAMMS223 study, 56 and two cases in another study.…”
Section: Alemtuzumab: T and B Cell Depleting Therapy For Rrmsmentioning
confidence: 99%
“…14 In MS, listeria meningitis was also reported in several cases with alemtuzumab 24 mg, 57 59 such as single cases of cerebral nocardiosis, 60 and Nocardia beijingesis . 58 In two pivotal studies, one case was reported in the CAMMS223 study, 56 and two cases in another study. 59 Dietary restriction of food such as unpasteurized milk and raw milk, a month before treatment with alemtuzumab was recommended to reduce the infection risk among patients.…”
Section: Alemtuzumab: T and B Cell Depleting Therapy For Rrmsmentioning
confidence: 99%